Związek wolności z prawdą - Grocholewski, Zenon (Studia Pastoralne, 2026)
The article is a philosophical-theological reflection on the relationship between freedom and truth. The author, using familiar texts as a background, especially documents of contemporary Popes, presents original and personal thoughts on the topic. The author attempts to assert that an honest attitude towards truth is a condition of freedom.